Enhancing critical thinking in physics education: developing an Arduino-based GMC as an innovative learning tool - Matsun Matsun; Adi Pramuda; Soka Hadiati; Hendrik Pratama (Journal of Education and Learning (EduLearn), 2026)
This research explores the development and innovative implementation of an Arduino Uno-based Geiger-Muller counter (GMC) as a physics learning tool designed to enhance students’ critical thinking skills. The aim was to address the gap in effective educational media in teaching radioactivity materials. This research used the analysis, design, development, implementation, and evaluation (ADDIE) model, which includes the analysis, design, implementation development, and evaluation stages. The sample of this study involved 165 students at University of PGRI Pontianak, using a pre-experimental design with one pretest-posttest group. Validation by experts and feedback from students confirmed the high validity and effectiveness of the media, with significant improvements seen in critical thinking indicators such as evaluation, analysis, interpretation, and inference. The use of real-world materials, including red Borneo agate testing, provided a practical context that enriched the learning experience. Although there was no control group, the findings suggest that integrating hands-on technology-based tools into physics education can significantly improve students’ critical thinking skills. This study contributes to the growing literature on educational innovation, offering practical solutions to improve critical thinking in science education through interactive and contextually relevant learning media.